The Meaning of Culture in Marketing Activities of Enterprises Worldwide - Selected Aspects - Sokół, Aneta (Znaczenie kultury w działaniach marketingowych przedsiębiorstw na całym świecie - wybrane aspekty, 2010)
The subject of the article is the notion of culture and its components. In the article close attention has been given to a discussion on cultural factors, which affect the decisions taken in preparation for advertising campaigns on foreign markets. Also, some examples of mistakes made due to the lack of knowledge of cultural differences in planning marketing activities in various countries are discussed.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 113, s. 796-806
Keywords: marketing; culture